Stereotype Threat and Performance how Self-Stereotypes Influence Processing by Inducing Regulatory Foci. [article] . - Seibt, Beate
The authors hypothesized that activated self-stereotypes can influence the strategies of task solution by inducing regulatory foci. More specifically, positive self-stereotypes should induce a promotion focus state of eagerness, whereas negative steroetypes should induce a prevention focus state of vigilance. Study 1 showed that a negative ascribed stereotype with regrds to task performance leads to better recall for avoidanc-related statements whereas a positive stereotype leads to better recall for approach-related statements. In studies 2 and 3, both an instrumental manipulation of group performance expectation and the preexisting stereotype of better verbal skills in women than in men led to faster and less accurate performance in the positive compared with the negative stereotype group. Studies 4 and 5 showed that positive in-group stereotypes led to more creative performance whereas negative stereotypes led to better analytical performance. These results point to a possible mechanism for stereotype-threat. -- (from the author)
Keywords: Psychology-Periodicals.